Factors affecting amplang production in Samarinda City, East Kalimantan Province - Augusta, Yanisa; Haqiqiansyah, Gusti; Fahrizal, Wahyu (Faculty of Fisheries and Marine Science, Mulawarman University, 2024)
This study uses several factors of production, namely capital, labor (HOK), and raw materials. The aims of this study were: (1) to determine the influence of production factors such as capital, labor (HOK) and raw materials; and (2) to find out what problems or obstacles are experienced during running a business. This research was conducted in Samarinda City, East Kalimantan Province. Primary data is obtained by observing and recording (observation) directly at the research location/object to be studied, as well as using direct interview techniques with respondents, namely business owners/employees. The sampling method for this research was carried out using a purposive sampling method, the samples selected based on these criteria were 30 businessmen processing amplangs/respondents. Methods of data analysis in this study used: (1) multiple linear regression analysis; (2) statistical test; (3) classic assumption test; and (4) descriptive analysis using computerized calculation tools such as Microsoft Excel Software and SPSS (Statistical Product And Service Solutions). The results showed that: Simultaneously (together), the capital input variable (X1), labor input (HOK) (X2) and raw material input (X3) had a significant effect on the amplang production variable (Yi), while partially, only labor input (HOK) (X2) and raw material input (X3) had a significant effect on the amplang production variable (Yi). The problems experienced by amplang processors were a decline in sales during the Covid-19 pandemic and a lack of availability of fish raw materials.